Performance of Concrete Containing Combination of Macro Mesh PP and Nylon Fibers - Muhammad Zul Asyraf Badri,; Faisal Sheikh Khalid, (Recent Trends in Civil Engineering and Built Environment, 2021)
Fibers are mainly used as substitutes for conventional reinforcement in non-structural applications to monitor early thermal contraction and drying shrinkage cracking. These benefits had increase the application of fibers to structures, especially those with low levels of durability such as grade slabs, foundation and walls. The use of fibers as part of the overall structural architecture increasing from time to time. The addition of an optimum combination of macro mesh polypropylene fibers and nylon fibers in concrete can enhance the strength and make it more durable. A few of researchers had done studies for the effect of combination of waste synthetic fiber in concrete. Therefore, this study was about to investigate the strength properties of concrete containing polypropylene fiber and nylon synthetic fibers as addition fiber materials. The design addition of fiber which 0.5%, 1.0% and 1.5% for both type of fibers was evaluated. In hybrid combinations, the strength is satisfactory without much reduction.  There are 36 samples that had been tested to determine the performance of concrete containing polypropylene fiber and nylon fiber as synthetic fiber. The study aims to produce and determine a concrete block that have the best compressive strength and tensile strength among the others. The expected result in this study are to known and produce the concrete block that have the greatest compression and tensile strength among the percentage of mixture listed. From the result obtained, workability of concrete containing macro mesh PP and nylon fiber as synthetic fibers had been done. So, conclusion that had been made was the combination of polypropylene fiber and nylon fiber as synthetic fiber had increase the performance of concrete and the 1.5% of mix proportion of polypropylene fiber and nylon fiber are the greatest percentage among others sample.